Existence and Uniqueness Theorems for Impulsive Fractional Differential Equations with the Two-Point and Integral Boundary Conditions - Mardanov, M. J.; Mahmudov, N. I.; Sharifov, Y. A. (Hindawi Ltd, 2014)
We study a boundary value problem for the system of nonlinear impulsive fractional differential equations of order alpha (0 < alpha <= 1) involving the two-point and integral boundary conditions. Some new results on existence and uniqueness of a solution are established by using fixed point theorems. Some illustrative examples are also presented. We extend previous results even in the integer case alpha = 1.
Keywords: Calculus